INTERNET CAFÉ INDUSTRY IN EAST BELITUNG - Hans Mohammad Hamim; Hariza Mailanda (Management and Leadership Study Programme, 2019)
Once became a phenomena all over Indonesia, the existence of browsing Internet Café (warnet) now just counting its day, especially in big cities. This paper is made to find out current situation of warnet in East Belitung (Beltim) and also to analyse causes of the current situation. Beltim was chosen as the area of study due to the area potential as a tourist destination. Two frameworks were employed: Industry Life Cycle framework and the Ansoff Matrix framework. Data collection methods used were both primary such as interview with warnet owners, warnet association, warnet users and government officers represented by the office of Integrated Investment and Licensing Services, the Ministry of Information and Communication. Secondary data used were books, journals, government reports and websites. The result of study indicated like in other areas, warnet business has passed its golden era and continue to shrink. Soon warnet browsing will be disappeared in East Belitung.